Penerapan Diskusi Kelompok dalam Meningkatkan Keaktifan Belajar Siswa Kelas X.2 dalam Mata Pelajaran Sosiologi di SMAN 4 Maros (Jurnal Motivasi Pendidikan dan Bahasa, 2024)
Group discussions are an effective method for increasing student participation in sociology learning. Through group discussions, students can interact, share ideas, and solve problems together. This encourages students' activeness in understanding sociological concepts, improves critical thinking skills, and builds better cooperation and communication between them.